Stakeholders and cooperation in higher education institutions - Marques, Ana Paula (2015)
ln the recent years, Portuguese Universities have diversified their strategies to promote entrepreneurial education among (under/post) graduates either through formal education or non-formal and informal activities. These activities are undertaken by different higher education stakeholders and key actors that may contribute to the construction of an entrepreneurial ecosystem and to raising the entrepreneurial spirit in (under/post) graduates. Therefore, it is possible to assume that the success of entrepreneurial learning can be related to the establishment of solid links and partnerships between higher education institutions, the government and the current labour market. From the ongoing project “Link.EES — Entrepreneurial Learrirg, Cooperation and the Labour Market: Good Practices in Higher Education” (POAT — ESF) we intend to contribute to the reflection regarding the added value of inter-organizational cooperation between the different entrepreneurial stakeholders involved in non-formal and informal learning in Portuguese Higher Education and the their impact on regional and national development.